(untitled) (Teaching and Learning Inquiry, 2022)
Instructor perspectives regarding the challenges they experience in enacting effective feedback processes have not been the focus in the literature on effective feedback processes. This study investigated the challenges that instructors experienced in providing effective feedback to students between January and April 2020, particularly considering campus closures and the shift to online learning in response to the COVID-19 pandemic. This study consisted of six focus groups held between January and April 2020 with five instructors from different disciplines at the same institution with class sizes ranging from 14 to 82. Through a thematic analysis using a constant comparison method, it was found that the biggest challenges instructors experienced in providing effective feedback was their own workload, the disruption that student inaction on feedback brought to the feedback process, and how the instructors managed their own affective responses and mindsets towards feedback. These findings are discussed within the context of the COVID-19 pandemic and based on these findings, recommendations for instructors include considering their own limitations when designing feedback processes and checking their beliefs about feedback with their students’ perspectives on feedback in order to align understanding.